The Language of Police Officers Matters: Factors Hampering Workplace English Writing Capability in the South African Police Services (SAPS) - Tebogo Johannes Kekana; Malesela Edward Montle (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
This article reports on the findings of an exploratory-based study about variables hampering adequate Workplace English writing competency of police officers in the South African Police Services (SAPS). The main assumption in this article is that this poor English writing proficiency that is tailored for the workplace in the as a result of many intertwined and interrelated factors. A quanti-qualitative research approach was adopted. Data was harvested using a questionnaire and in-depth interviews from 203 research participants from various police stations in Gauteng Province of South Africa. Thematic Content Analysis (TCA) was used for analysis of qualitative data. Quantitative data was analysed using SPSS (Statistical Package for Social Sciences). The investigation was underpinned by Work Integrated Learning (WIL), Genre and NA (Needs Analysis) theories. The investigation found that there is a deficiency of expertise as far as pedagogy is concerned among police trainers. Furthermore, the study revealed that the absence of tertiary qualifications contributes to the problem. Language teaching in the SAPS training colleges is found not to be given adequate emphasis. Lastly, the over-domination of physical training over academic teaching was also a challenge. This investigation underscores the crucial aspect of reflective research as a source of information.